Pengaruh Persepsi Siswa Tentang Pembelajaran Hybrid dan Cara Belajar Terhadap Hasil Belajar Ekonomi Siswa Kelas XI IPS Di SMAN 1 Pariangan - Mulda Ladya; Syamwil Syamwil (Jurnal Salingka Nagari, 2023)
The purpose of this study is to determine 1) the effect of students' perceptions of hybrid learning and learning methods on the economics learning outcomes of students at SMAN 1 Pariangan, 2) the effect of students' perceptions of hybrid learning on the economics learning outcomes of students at SMAN 1 Pariangan, and 3) the effect of learning methods on the economics learning outcomes of students at SMAN 1 Pariangan. The population consisted of all 146 students from Class XI Social Sciences at SMA Negeri 1 Pariangan with proportional random sampling technique. Multiple linear regression was used to analyze the data. The result of this study, (1) students' perceptions of hybrid learning and learning methods had a positive and significant effect on the economics learning outcomes of students at SMA N 1 Pariangan, (2) students' perceptions of hybrid learning had a positive and significant effect on the economics learning outcomes of students at SMA N 1 Pariangan, and (3) How to learn has a positive and significant effect on the outcomes of students at SMA N 1 Pariangan.